Comparison Grounds for Construction Contracts Termination under UAE Law and FIDIC Standard Contracts - ALBAHAR, ISMAIL ABDULLA (2018)
Termination rights in relation to a contract are significant as a practical way of applying pressure on other party in the contract. However, exercising the rights of termination ought to be approached using extreme caution. International Federation of Consulting Engineers (FIDIC) is a global body tasked with developing rules and regulations that ought to be put into consideration in the process of engaging in construction contracts. Thus, this body provides special guidelines on the conditions that parties follow while engaging in construction contracts. It also provides regulations for the grounds for construction contracts termination. On the other hand, the United Arab Emirates has its own specific provisions as it relates to terminating construction contracts. The provisions of United Arab Emirates are enacted from statutes and the civil code of this nation. As a consequence, there are various variations in the utilization of the grounds for the termination of construction contracts. Similarities also exist in relation to the application of the construction contract termination in tandem to these forenamed laws. However, there is laxity in the application of the provisions for the grounds on the termination of construction contracts. In this case, the UAE has to ensure that it enhances fairness in the application of the grounds for the termination of construction contracts. It is necessary to explore the comparisons between the UAE law and FIDIC Standard Contracts by looking at both contractual laws to establish the grounds on which they appear to be similar so that the context of their application is related and the standpoint of the disparities in their applicability. There is also the need for reviewing the conditions related to the termination of the contract based on the assertions by the laws of the United Arab Emirates and the FIDIC terms connected to the effective termination of construction contracts.